2011
DOI: 10.1093/jnci/djr114
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Family Cancer History Reported in a Population-Based Survey

Abstract: General population reports on family history for the four major adult cancers were not highly accurate. Efforts to improve accuracy are needed in primary care and other health-care settings in which family history is collected to ensure appropriate risk assessment and clinical care recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 28 publications
3
86
0
Order By: Relevance
“…For first-degree relatives, previous studies have however found reported ovarian cancer history to be reasonably accurate (83.3% probability of agreement between reported ovarian cancer status in first-degree relatives and status according to reference standard, 95% CI 72.8 to 93.8) 23 24. A further drawback of our study is the lack of information on tumour subtypes in relatives.…”
Section: Discussionmentioning
confidence: 64%
“…For first-degree relatives, previous studies have however found reported ovarian cancer history to be reasonably accurate (83.3% probability of agreement between reported ovarian cancer status in first-degree relatives and status according to reference standard, 95% CI 72.8 to 93.8) 23 24. A further drawback of our study is the lack of information on tumour subtypes in relatives.…”
Section: Discussionmentioning
confidence: 64%
“…With respect to family history, sharing cancer information within families and the accuracy of reporting depends on multiple factors such as geographical distance, familial culture of communication, degree of relatedness, gender, and knowledge about cancer (34)(35)(36). Reporting of first-degree relatives and breast cancer is generally more accurate than reporting of second-degree relatives and other cancers (37)(38)(39), with ovarian cancer often underreported (38,39). Because the USPSTF risk classification depends on the number and relatedness of affected relatives, an underreporting of ovarian cancer may have led to an underestimation of the number of women at high-risk.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer analyses will also include previous benign breast disease (fibrocystic disease, intraductal papilloma or fibroadenoma) 49. The results will also be adjusted for family history of cancer50 (this will vary according to the cancer under consideration) if recorded 6 months before the index date. This is to reduce family recall bias as cases are more likely to report a family history of cancer around the time of diagnosis 51…”
Section: Methods and Analysismentioning
confidence: 99%